Environmental determinants of polycyclic aromatic hydrocarbons exposure at home, at kindergartens and during a commute. (September 2018) - Miri, Mohammad; Alahabadi, Ahmad; Ehrampoush, Mohammad Hassan; Ghaffari, Hamid Reza; Sakhvidi, Mohammad Javad Zare; Eskandari, Mahboube; Rad, Abolfazl; Lotfi, Mohammad Hassan; Sheikhha, Mohammad Hassan
Abstract: The aim of this study was to assess the potential health risk of exposure to polycyclic aromatic hydrocarbons (PAHs) at home and kindergarten for pre-school children. The urine samples were taken from 200 pre-school children aged 5–7 years and analyzed for 1-OHP as a biomarker of PAHs. Mixed effect models were applied to investigate the association between effective environmental parameters (mode of transport, distance to major roads, traffic density, greenness, tobacco exposure, home ventilation, and grill foods) and urinary 1-OHP levels. A Monte-Carlo simulation technique was applied to calculate the risk of exposure to PAHs and to check the uncertainty of input variables and the sensitivity of the estimated risk. The median and inter quartile range (IQR) of 1-OHP was 257 (188.5) ng L −1 . There was a positive significant association between distance from the kindergartens to the green space with surface area ≥5000 m 2 and 1-OHP concentration (β = 0.844, 95% CI: 0.223, 1.46, P-value = 0.009). Also, urinary 1-OHP was found to be inversely associated with the time the window was open at the home (β = −12.56, 95% CI: −23.52, −1.596, P-value = 0.025) and normalized difference vegetation index (NDVI) in a 100 m buffer around the homes. The mean (9.76 E-3) and 95th percentile (3.28 E-2) of the hazard quotient (HQ) indicated that the concentration of urinary 1-OHP is at a safe level for the target population (HQ < 1). According to the sensitivity analysis results, the concentration of 1-OHP is the most influential variable in the estimated risk. Our findings indicated that the proximity of homes and kindergartens to green space areas and their remoteness from the main streets and heavy traffic areas are associated with reduced exposure to PAHs. Highlights: 1-OHP was measured in the urine of 200 pre-school children. The association between different environmental variables and 1-OHP concentration were investigated. An inverse association were found between greenness and 1-OHP concentration. The mean and 95th percentile of HQ was at the safe level (HQ < 1).